ПРАВОВОЙ СТАТУС СУБЪСКТОВ СУДЕБНОЭКСПЕРТНОЙ ДЕЯТЕЛЬНОСТИ В УГОЛОВНОМ ПРОИЗВОДСТВЕ - Ткаченко, Наталья Николаевна (SUPREMANCE OF LAW, 2016)
The article substantiates the relevance of the study of the legal status of forensic activity subjects in criminal proceedings. It turns out the nature and content of the legal status of forensic activity subjects in criminal proceedings. We analyze the provisions of regulations that determine the rights and obligations ofl experts. The author highlights the conditionality of the legal status of these entities and their professional and procedural status.